A framework for human-centered production planning and control in smart manufacturing. (October 2022) - Kessler, Melanie; Arlinghaus, Julia C.
Abstract: Smart manufacturing systems have to meet high performance expectations in form of customer individual products, short lead times, high due date reliability and resilience by the integration of new technologies and by intelligent process design. The planning and control of such smart manufacturing systems necessitates several instances of human decision-making. The latest research at the nexus of operations management and psychology reveals that human decision-making in such fast-paced, dynamic and complex environments is often biased, resulting in suboptimal operational performance. Human-centered design of planning and control processes can mitigate biased decisions, thus boosting performance in smart manufacturing systems. Current research is silent about the impact and mitigation of cognitive biases in operations management, though. We intend to close this research gap. We combine systematic reviews of literature on behavioral operations management and cognitive biases in operations management, particularly in production planning and control with an in-depth case study based on 12 expert interviews. We explore two decision-making models and combine them in a PPC framework. We create a framework for human-centered PPC in smart manufacturing systems, which includes the main impact factors, challenges and performance capabilities. Based on a detailed case study of a steel producer, we present a framework of human-centered PPC comprising five hypotheses on the impact of cognitive biases on human decision-making and on manufacturing performance. Highlights: Synthesis of psychology and PPC literature stream showing the influence of biased decision-making. Different decision types lead to different level of influence of cognitive biases. Research base of in-depth case study and 12 expert interviews. Framework deriving five hypotheses about the impact of CB on human decision-making in PPC.